2018
DOI: 10.1016/j.neuroimage.2016.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sodium MR imaging: A review of its evolving role in medicine

Abstract: Sodium magnetic resonance (MR) imaging in humans has promised metabolic information that can improve medical management in important diseases. This technology has yet to find a role in clinical practice, lagging proton MR imaging by decades. This review covers the literature that demonstrates that this delay is explained by initial challenges of low sensitivity at low magnetic fields and the limited performance of gradients and electronics available in the 1980s. These constraints were removed by the introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(153 citation statements)
references
References 295 publications
(300 reference statements)
1
142
1
Order By: Relevance
“…Previous authors have demonstrated increased TSC within CNS neoplasms such as high‐grade glioma, and that 23 Na MRI can be used as a predictive marker of both tumor grade and prognosis . Within glioma, cellular proliferation and changes in cell membrane ion transporters contribute to elevated intracellular sodium concentrations, but these tumors also display increases in the sodium‐rich extravascular–extracellular space secondary to necrosis and loss of normal cellular packing . Evidence from in vivo animal studies of temporal 23 Na MRI changes in glioma following chemotherapy treatment suggest that TSC may also serve as an early marker of progression and treatment response in this tumor group .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors have demonstrated increased TSC within CNS neoplasms such as high‐grade glioma, and that 23 Na MRI can be used as a predictive marker of both tumor grade and prognosis . Within glioma, cellular proliferation and changes in cell membrane ion transporters contribute to elevated intracellular sodium concentrations, but these tumors also display increases in the sodium‐rich extravascular–extracellular space secondary to necrosis and loss of normal cellular packing . Evidence from in vivo animal studies of temporal 23 Na MRI changes in glioma following chemotherapy treatment suggest that TSC may also serve as an early marker of progression and treatment response in this tumor group .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown intracellular sodium volume to be significantly higher in malignant tumors compared with benign lesions due to increased cell density, altered metabolism, and changes in cell membrane ion transporters . In addition to this increase in intracellular sodium, many malignant tumors also show an increase in the sodium‐rich extravascular–extracellular space, which in some cases may be secondary to an increase in necrosis . Combining information on sodium concentration from both the intracellular and the extracellular compartments provides complementary information that can be used to probe tissue structure, cell density, and membrane integrity in more detail, which could be used in the assessment of tumor progression and treatment response .…”
mentioning
confidence: 99%
“…23 Na MRI has been frequently applied to investigate diseases such as stroke, tumor, multiple sclerosis, and cartilage degradation . This focus is attributed to the high prevalence of these diseases and the connection of Na + concentration to pathophysiology.…”
Section: Physiologymentioning
confidence: 99%
“…The exact onset time is often unknown, albeit being crucial for treatment decisions. A prospective biomarker to determine the onset time and to characterize tissue viability is the tissue sodium concentration (TSC) threshold …”
Section: Physiologymentioning
confidence: 99%
“…Disturbances of this delicate balance provide a sensitive, early indicator for cell breakdowns and give an insight into cell integrity and tissue viability. With sodium nuclei providing the second strongest MR‐signal in biological tissue, sodium MRI offers promising potential as a clinical biomarker with capabilities ranging from early diagnosis to therapy response monitoring as well as the detection of diseases without anatomical abnormalities . Because of hardware advancements, the number of sodium MRI studies is steadily increasing ranging across a variety of diseases encompassing stroke, tumors, neurodegenerative diseases, and musculoskeletal pathologies …”
Section: Introductionmentioning
confidence: 99%